J-integral evaluation and structural integrity assessment using FAD for SA 312 Type 304 LN steel welded pipes with notch under monotonic loading (Fracture and Structural Integrity, 2025)
In the present study, structural integrity of SA312 Type 304 LN steel welded pipes with through-wall crack under monotonic loading has been assessed using failure assessment diagram (FAD). Plastic capacity utilization and fracture capacity utilization are compared simultaneously using a FAD. Material’s initiation fracture toughness and J-integral evaluated using load-CMOD method were used for evaluating fracture resistance were used for generation of failure assessment diagrams. Various analytical expressions proposed by Zahoor (1989) and Takahashi (2002) were used to evaluate limit load moment (plastic capacity). Various approaches for deriving the failure assessment line were considered in this study viz, BS 7910 2A, BS 7910 2B, and SINTAP. The failure assessment lines constructed using SINTAP, BS 7910 2A level and BS 7910 2B level for SA312 Type 304 LN steel procedures yielded similar results. Limit load moment values from Takahashi were lower and hence resulted in assessment points closer to the failure assessment lines. Structural integrity assessment is very significant in deciding the safety of operation of the piping components.
Keywords: Failure assessment diagram; J-integral; Welded pipes; Circumferential through wall notch; Monotonic loading